A Randomized Controlled Trial of Communication Training with Primary Care Providers to Improve Patient-Centeredness and Health Risk Communication - Helitzer, Deborah L. (2010)
OBJECTIVE: To determine the efficacy and effectiveness of training to improve primary care providers’ patient-centered communication skills and proficiency in discussing their patients’ health risks. METHODS: Twenty-eight primary care providers participated in a baseline simulated-patient interaction and were subsequently randomized into intervention and control groups. Intervention providers participated in training focused on patient-centered communication about behavioral risk factors. Immediate efficacy of training was evaluated by comparing the two groups. Over the next three years, all providers participated in two more sets of interactions with patients. Longer term effectiveness was assessed using the interaction data collected at 6 and 18 months post training. RESULTS: The intervention providers significantly improved in patient-centered communication and communication proficiencies immediately post-training and at both follow-up time points. CONCLUSIONS: This study suggests that the brief training produced significant and large differences in the intervention group providers which persisted two years after the training. PRACTICE IMPLICATIONS: The results of this study suggest that primary care providers can be trained to achieve and maintain gains in patient-centered communication, communication skills and discussion of adverse childhood events as root causes of chronic disease.